2020
DOI: 10.1111/jopy.12544
|View full text |Cite
|
Sign up to set email alerts
|

Is the negative always that bad? Or how emotion regulation and integration of negative memories can positively affect well‐being

Abstract: Objective The purpose of this study was to determine whether coherent integration of negative memories into the self could positively predict well‐being over time, and whether certain emotion regulation strategies could facilitate this coherent integration. In turn, coherent integration of negative memories was expected to further facilitate adaptive emotion regulation strategies over time. Method A total of 303 participants took part in this longitudinal study. At Phase 1, they completed measures of emotion r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…For example, Roth et al (2014, 2018) found participants in an integrative emotion regulation condition displayed greater reduction in experienced fear and physiological arousal during a second exposure to a fear‐eliciting scene and recalled more details than participants in an expressive suppression condition (Roth et al, 2014) or an emotional distancing condition (Roth et al, 2018). Houle and Philippe (2020) recently showed that while participants high on integrative emotion regulation and those high on dysregulation both reported significant memories of a negative event, the former had higher acceptance of it, which, in turn, predicted increased well‐being. In another study of well‐being, Brenning, Soenens, Van Petegem, and Vansteenkiste (2015) found adolescents' integrative emotion regulation was positively related with self‐esteem, while suppressive emotion regulation and dysregulation were negatively associated.…”
Section: Sdt and Emotion Regulationmentioning
confidence: 99%
“…For example, Roth et al (2014, 2018) found participants in an integrative emotion regulation condition displayed greater reduction in experienced fear and physiological arousal during a second exposure to a fear‐eliciting scene and recalled more details than participants in an expressive suppression condition (Roth et al, 2014) or an emotional distancing condition (Roth et al, 2018). Houle and Philippe (2020) recently showed that while participants high on integrative emotion regulation and those high on dysregulation both reported significant memories of a negative event, the former had higher acceptance of it, which, in turn, predicted increased well‐being. In another study of well‐being, Brenning, Soenens, Van Petegem, and Vansteenkiste (2015) found adolescents' integrative emotion regulation was positively related with self‐esteem, while suppressive emotion regulation and dysregulation were negatively associated.…”
Section: Sdt and Emotion Regulationmentioning
confidence: 99%
“…Six items assessed dysregulation, and a sample item was “I often behave under the influence of my negative emotions, even if I don't want to behave like that” ( α = .82). This scale has shown adequate evidence of reliability and validity in past research (Houle & Philippe, ; Roth et al, ).…”
Section: Methodsmentioning
confidence: 93%
“…We used the scale developed by Roth and colleagues (, , ), which taps into these three factors of emotion regulation styles, that they, respectively, labeled integrative regulation, controlling regulation, and dysregulation. We used a slight adaptation of this scale to assess the regulation of negative emotions in general (Houle & Philippe, ) instead of the regulation of a specific emotion (e.g., fear, anger), as assessed by the initial scale. Participants indicated their degree of agreement with each item, on a 7‐point Likert scale (1 = Disagree strongly , 7 = Agree strongly ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested that experiencing negative and positive emotions is beneficial for well-being ( Dejonckheere et al, 2019 ; Quoidbach et al, 2014 ). Negative emotions are not always bad ( Houle & Philippe, 2020 ; Tamir, 2016 ). Experiencing both positive and negative emotions also means that individuals are attentive to their emotions and have emotional clarity to facilitate their thoughts.…”
Section: Discussionmentioning
confidence: 99%